The Impact of Parent-Child Relationships on the Emotional State of Children with Cancer Undergoing Long-Term Treatment - Yu.P. Zamyshliaeva; Yu.E. Kurtanova (Клиническая и специальная психология)
This study is devoted to identifying the interrelationship of child-parent relations and emotional state of children with cancer who are on long-term treatment. The research methodology includes a complex of psychodiagnostic methods for studying the emotional state of children and child-parent relationships: questionnaire “Parent-child interaction” by I.M. Markovskaya, family sociogram, projective technique “Non-existent animal”, “Train” by S.V. Velieva, anxiety test by A.M. Prikhozhan for younger schoolchildren and anxiety test by R. Temml, M. Dorki and V. Amen for preschoolers. Children aged 5–10 years and their parents participated in the study. 30 children and 30 parents were interviewed on the basis of the hospital school of the “TeachKnow” project at the Federal State Budgetary Institution National Medical Research Center of Oncology named after N.N. Blokhin, Ministry of Health of Russia. The results obtained indicate a correlation between the specifics of child-parent relations and the emotional state of children with cancer.